Language- and culture-adapted care for the Sami people – is it possible? Experiences from a development effort in four regions - Stål, Ann-Jeanett; Kling, Sofia; Daerga, Laila (Socialmedicinsk tidskrift, 2021)
This article describes some of the lessons that the Knowledge Network for Sami Health has learned in four years of working with Sami healthcare development. The article describes challenges and opportunities in the area, and sheds light on the potential for future development. The Knowledge Network for Sami Health is a collaborative effort between Region Norrbotten, Region Västerbotten, Region Jämtland Härjedalen, Region Dalarna, the Sami Parliament and multiple Sami organisations. The article provides an outline background of why healthcare needs to be adapted to Sami people. The article sheds light on the need for increased Sami cultural competence to improve the interaction and communication between Sami patients and those working in the health care system. Other identified challenges are geographic and linguistic accessibility, and the fact that the existing Sami competence amongst health care professionals has not been used in a purposeful way. The article ties into on-going change efforts for sustainable healthcare. Interesting areas of development that are being explored are: 1) Internal and external collaboration with municipalities, regions and across national borders that are central to addressing the challenges that exist with a language- and culture-adapted care. 2) Digital solutions as a possibility to make the existing Sami competence available and synergetic. 3) Sami participation as fundamental to confidence and trust.